Immigration modulates audiovisual emotional processing in adults: is this really an influence of the host culture? - Anna K. Nakamura; Anna K. Nakamura; Hisako W. Yamamoto; Hisako W. Yamamoto; Sachiko Takagi; Tetsuya Matsuda; Hiroyuki Okada; Chiaki Ishiguro; Chiaki Ishiguro; Akihiro Tanaka (Frontiers in Psychology)
IntroductionIndividuals from Western cultures rely on facial expressions during the audiovisual emotional processing of faces and voices. In contrast, those from East-Asian cultures rely more on voices. This study aimed to investigate whether immigrants adopt the tendency of the host culture or whether common features of migration produce a similar modification regardless of the destination.MethodsWe examined how immigrants from Western countries to Japan perceive emotional expressions from faces and voices using MRI scanning.ResultsImmigrants behaviorally exhibited a decrease in the influence of emotions in voices with a longer stay in Japan. Additionally, immigrants with a longer stay showed a higher response in the posterior superior temporal gyrus, a brain region associated with audiovisual emotional integration, when processing emotionally congruent faces and voices.DiscussionThese modifications imply that immigrants from Western cultures tend to rely even less on voices, in contrast to the tendency of voice-dominance observed in native Japanese people. This change may be explained by the decreased focus on prosodic aspects of voices during second language acquisition. The current and further exploration will aid in the better adaptation of immigrants to a new cultural society.